1995
DOI: 10.1007/bf00197749
|View full text |Cite
|
Sign up to set email alerts
|

Differing afferent connections of spiking and nonspiking wind-sensitive local interneurons in the terminal abdominal ganglion of the cricket Gryllus bimaculatus

Abstract: Fifteen local spiking interneurons (LSIs) andtwenty-one local nonspiking interneurons (LNIs) were identified in the terminal abdominal ganglion (TAG) of the cricket Gryllus bimaculatus on the basis of intracellular recording and staining (Figs. 1, 5, 6). Although the majority of LNIs showed sharp directionalities (Fig. 7) the LSIs did not (Fig. 3). The directionality of LNIs varied with the recording sites within a single cell (Fig. 8). Electrical stimulations of the cercal sensory nerve suggested that the LNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…As inhibitory information must be relayed by at least one local interneuron as mentioned above, excitatory inputs to the GIs must also be polysynaptically relayed. The polysynaptical excitatory neural pathways in the cricket cercal system have also been suggested in the previous study dealing with local interneurons (Baba et al, 1995).…”
Section: Polysynaptic Inhibitory and Excitatory Neural Pathwaysmentioning
confidence: 59%
See 1 more Smart Citation
“…As inhibitory information must be relayed by at least one local interneuron as mentioned above, excitatory inputs to the GIs must also be polysynaptically relayed. The polysynaptical excitatory neural pathways in the cricket cercal system have also been suggested in the previous study dealing with local interneurons (Baba et al, 1995).…”
Section: Polysynaptic Inhibitory and Excitatory Neural Pathwaysmentioning
confidence: 59%
“…Since directional characteristics of inhibition are different from GI to GI, different types and/or numbers of local interneurons in the cricket cercal system (Kobashi and Yamaguchi, 1984;Baba et al, 1995) must be recruited for mediating inhibitory information.…”
Section: Polysynaptic Inhibitory and Excitatory Neural Pathwaysmentioning
confidence: 99%
“…The effects of neuron morphology can be sufficient to introduce significant errors in measurement of conductance [Rall et al, 1992;Hartline and Castelfranco, 2003] and synaptic [Williams and Mitchell, 2008] properties. The importance of neuron morphology is further demonstrated by the consistent across-animal neuron morphologies present in some systems [Robertson and Pearson, 1983;Bacon and Murphey, 1984;Miller and Jacobs, 1984;Murphey et al, 1984;Baba et al, 1995].…”
Section: Introductionmentioning
confidence: 96%
“…The method has been extensively used to demonstrate the directionality of the cercal system, beginning with the use of directional oscillatory sound stimuli (Tokareva and Rozhkova, 1973;Edwards and Palka, 1974;Palka and Olberg, 1977), and later being refined to stimuli consisting of single puffs of air (Westin et al, 1977;Tobias and Murphey, 1979;Westin, 1979;Aldworth et al, 2008;Miller and Jacobs, 1984;Jacobs and Miller, 1985;Jacobs et al, 1986;Miller et al, 1991;Theunissen and Miller, 1991;Bodnar et al, 1991;Baba et al, 1991;Baba et al, 1995;Kolton and Camhi, 1995) (Z.A., A. G. Dimitrov, G. Cummins, T. Gedeon and J.P.M., manuscript submitted). In one set of experiments, it was shown that two bilateral pairs of interneurons (10-2a and 10-3a) formed a functional unit capable of detecting air particle displacement at moderate velocities from all 360° of space in the horizontal plane Theunissen and Miller, 1991).…”
Section: Neural Coding In the Cricket Cercal Systemmentioning
confidence: 99%